Carcinoembryonic antigen is a sialyl Lewis x/a carrier and an E-selectin ligand in non-small cell lung cancer - Ferreira, Inês Gomes (Int J Oncol, 2019)
The formation of distant metastasis resulting from vascular dissemination is one of the leading causes of mortality in non-small cell lung cancer (NSCLC). This metastatic dissemination initiates with the adhesion of circulating cancer cells to the endothelium. The minimal requirement for the binding of leukocytes to endothelial E-selectins and subsequent transmigration is the epitope of the fucosylated glycan, sialyl Lewis x (sLe(x)), attached to specific cell surface glycoproteins. sLe(x) and its isomer sialyl Lewis a (sLe(a)) have been described in NSCLC, but their functional role in cancer cell adhesion to endothelium is still poorly understood. In this study, it was hypothesised that, similarly to leukocytes, sLe glycans play a role in NSCLC cell adhesion to E-selectins. To assess this, paired tumour and normal lung tissue samples from 18 NSCLC patients were analyzed. Immunoblotting and immunohisto-chemistry assays demonstrated that tumour tissues exhibited significantly stronger reactivity with anti-sLe(x)/sLe(a) antibody and E-selectin chimera than normal tissues (2.2- and 1.8-fold higher, respectively), as well as a higher immunoreactive score. High sLe(x)/sLe(a) expression was associated with bone metastasis. The overall α1,3-fucosyltransferase (FUT) activity was increased in tumour tissues, along with the mRNA levels of FUT3, FUT6 and FUT7, whereas FUT4 mRNA expression was decreased. The expression of E-selectin ligands exhibited a weak but significant correlation with the FUT3/FUT4 and FUT7/FUT4 ratios. Additionally, carcinoembryonic antigen (CEA) was identified in only 8 of the 18 tumour tissues; CEA-positive tissues exhibited significantly increased sLe(x)/sLe(a) expression. Tumour tissue areas expressing CEA also expressed sLe(x)/sLe(a) and showed reactivity to E-selectin. Blot rolling assays further demonstrated that CEA immunoprecipitates exhibited sustained adhesive interactions with E-selectin-expressing cells, suggesting CEA acts as a functional protein scaffold for E-selectin ligands in NSCLC. In conclusion, this work provides the first demonstration that sLe(x)/sLe(a) are increased in primary NSCLC due to increased α1,3-FUT activity. sLe(x)/sLe(a) is carried by CEA and confers the ability for NSCLC cells to bind E-selectins, and is potentially associated with bone metastasis. This study contributes to identifying potential future diagnostic/prognostic biomarkers and therapeutic targets for lung cancer.